Real-Time Internet-Based Master Schedule Monitoring to Reduce Late Penalty Costs in Housing Projects - Mulyadi Sugih Dharsono (Green Publisher Indonesia, 2025)
Delays in handover to consumers will result in real estate developer companies being fined by consumers. This is a burden that burdens the financial position of development companies which can reach losses of hundreds of millions or even billions of rupiah. The appearance of the fine greatly affects the company's cash flow, because the company's profit is eroded to pay the fine. Housing project development activities, especially landed houses projects, are very complex and require cooperation between departments from planning, implementation to consumer handover. Complexity occurs where many parties involved in one cycle have strict targets and influence each other, so it needs to be outlined in a time frame called a master schedule. It requires a thorough and detailed master schedule control to map the conditions and problems that arise as well as trouble-shooting in the existing time frame. With good master schedule control , it will result in on-time handover to consumers. So that it will reduce the company's cash flow burden because it pays consumer fines. Through observation and interview methods conducted in the period of 2016-2019, the author took a study on one of the developers of a housing project in Serpong, Tangerang, from a total of 7 (seven) clusters, data showed that there was 18% of late consumer handovers resulting in fines. The results of this project management study , namely an integrated project time management system based on the internet, special servers and cloud, can provide an overview of solutions to reduce late fines.